2013
DOI: 10.1155/2013/397278
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Status of Homologous Proteins of Biomineralization (Biosilicification) in the Taxonomy of Phylogenetic Domains

Abstract: The taxonomic affiliation (in the systematisation of viruses, and biological domains) of known peptides and proteins of biomineralization (silicateins, silaffins, silacidins and silicase) and their primary structure homologues were analyzed (methods in silico; using Uniprot database). The total number of known peptides and proteins of biosilicification was counted. The data of the quantitative distribution of the detected homologues found in nature are presented. The similarity of the primary structures of sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, contrary to plants, the process of biosilicification is well understood in diatoms [ 20 ]. The functional characterization of biosilicification-related proteins in diatoms did not help much in the identification of proteins involved in this process because of no sequence homology between plant and diatom silicification proteins [ 21 , 22 ]. So far, the research in nonplant lineage biosilicification has demonstrated that the silicification related proteins must have certain features such as proline, lysine, and glutamine-acid-rich (P, K, E-rich) domain(s), RXL domain [ 23 , 24 ], and several proline residues [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, contrary to plants, the process of biosilicification is well understood in diatoms [ 20 ]. The functional characterization of biosilicification-related proteins in diatoms did not help much in the identification of proteins involved in this process because of no sequence homology between plant and diatom silicification proteins [ 21 , 22 ]. So far, the research in nonplant lineage biosilicification has demonstrated that the silicification related proteins must have certain features such as proline, lysine, and glutamine-acid-rich (P, K, E-rich) domain(s), RXL domain [ 23 , 24 ], and several proline residues [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This group is extremely widespread across the phylogenetic tree of plants. We hypothesized that matrix peptides and proteins (silaffins and silacidins) could be among the most ancient matrix substances of biomineralization [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The search for homologues of typical representatives of silicon transporters (SITs), aquaporins, silaffins, silicateins, silacidins, and silicase (peptides and proteins of diatoms, sponges, rice, and corn were chosen), in the nucleotide sequence bases, was conducted using BLAST ( http://blast.ncbi.nlm.nih.gov ) as described in the paper [ 33 ]. From the Uniprot base (March 2014), we obtained the amino acid sequences of SIT (ID O81199 and C7G3B4), aquaporin (ID Q6Z2T3), silaffins (ID Q9SE35, Q5Y2C0 and Q5Y2C2), and silicateins (ID B5B2Z1, B1GSK9, and B5LT52).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, 80 different proteins have already been researched regarding the formation of hydrated silicon dioxide structures, such as occur in diatoms and glass sponges (Fig. 1) 23 . Image reproduced with kind permission 22 .…”
Section: Biomimetic Synthesis By Regulating Organic Macromoleculesmentioning
confidence: 99%